Basic Considerations of Judges in Imposing Criminal Code Article 81 Paragraph 2 of the Child Protection Law Against Children Who Have Sexual Intercourse on the Basis of Consent - Muhammad Fathony Rizky Noorizain; Fachrizal Afandi; Prija Djatmika (CV. AFDIFAL MAJU BERKAH, 2023)
In this study, the author raises the issue of the basis of the judge's consideration in imposing punishment on children who commit Copulation on the basis of mutual consent. This is motivated because it is not clearly regulated in the Child Protection Law regarding the crime of sexual intercourse committed by a child if the sexual intercourse is carried out on the basis of mutual consent without any element of violence or persuasion from the perpetrator to the victim, causing a vacuum of norms. The formulation of this problem is How is the evidentiary arrangement of the case of sexual intercourse committed by a child on the basis of mutual consent in Indonesia and What is the basis for the judge's consideration in imposing a criminal decision based on Article 81 paragraph (2) of the Child Protection Law against children who have sexual intercourse on the basis of mutual consent. The objectives in this study are (1) To know and analyze the criminal proof of sexual intercourse committed by children on the basis of mutual consent in Indonesian criminal law enforcement. (2) To know and analyze the basis of the judge's consideration in handing down a verdict against minors who have consensual sexual intercourse. To analyze this problem, the theories that will be used as guidelines for analysis are the theory of evidence, the theory of justice, expediency and legal certainty. This type of research uses normative legal methods consisting of a statutory approach (statue approach), conceptual approach (conceptual approach) and case study approach (case law). The results of this study, the author concludes that the Child Protection Law does not recognize the term consensual because the position in child sexual intercourse against children who are consensual, children are seen in the position of victims. Although in the proof the act is done consensually or child fornication. The criminal regulation is regulated in Article 81 of Law Number 35 of 2014 concerning Child Protection